ANALISIS KINERJA KOPERASI SIMPAN PINJAM "TANI MAKMUR" KABUPATEN BANTUL DENGAN METODE BALANCED SCORECARD - Khottul Azizah; Suhatmi Hardyastuti; Any Suryantini (Agro Ekonomi, 2015)
Performance assessment is important to be known as a tool of data analysis, accountability and decision making. Performance assessment is done to observe bothfinancial aspect and non-jinancial aspect by using Balanced Scorecard method. Balanced Scorecard become the base of Peraturan Menteri Negara Koperasi dan Usaha Kecil Menengah Republik Indonesia Nomor 14/Per/M.KU/KM/XII/2009 about a tool of health assessment for Savings andLoans Cooperative. The aspects that are being analyzed are capital, productive asset quality, management, efficiency, liquidity, independence of growth, and cooperative identity .. This study aims to find out the financial & non-financialperformance of KSP "Tani Makmur" Bantul Regency period 2009-2013. The kind of research is descriptive. The results showed that (1) From seven aspects assessed, aspect capital and liquidity aspect showing the worse conditionthan other aspect. (2) Aspect eficiency showing the best result (3) the helath level of KSP Tani Makmur in 2009-2013 is "Healthy Enough". Based on the result of this study, it s excpected that KSP "Tani Makmur" can improve theirfinancial and non financial performance.